Inside a marine harbour: Patterns of distribution and abundance of Mytilus galloprovincialis in the Port of Sines - Santo, Cristina Isabel Oliveira Espírito (2015)
Dentro do Porto de Sines, mexilhões são abundantes em paredes verticais e boias, e ausentes em molhes horizontais; fora do porto, são comuns monoculturas de mexilhões em praias rochosas. Como primeiro objetivo, foram estudados os padrões de distribuição, abundância e estrutura dimensional de mexilhões, e três fatores que geram padrões: predação, stress térmico e recrutamento. Foram obtidas diferenças significativas entre orientações dentro do porto (verticais vs. horizontais) e entre áreas dentro vs. fora, com efeitos significativos de predação e stress térmico. Registou-se recrutamento em todas as áreas; porém, os três fatores não definiram um padrão de distribuição e abundância de mexilhões dentro do porto. O segundo objetivo consistiu num estudo preliminar da morfologia de mexilhões. Foram analisados caracteres qualitativos e morfométricos em três ambientes, sendo significativamente úteis para separar mexilhões de cada área dentro e fora do porto. Os resultados foram insuficientes para discriminar semelhanças ou diferenças características de uma ou duas espécies. /ABSTRACT - lnside the Port of Sines, mussels are abundant in vertical seawalls and buoys, and absent in horizontal breakwaters; outside the port, mussels form patchy monocultures in rocky shores. As a first objective, the patterns of distribution, abundance and dimensional structure of mussels were studied, and three processes that generate patterns: predation, thermal stress, and recruitment. Differences were apparent between orientations inside the port (vertical vs. horizontal) and among areas inside vs. Outside, with significant effects of predation and thermal stress. Recruits were present in all areas; however, the three processes didn't explain the distribution and abundance of mussels inside the port. The second objective consisted in a preliminary study of the morphology of mussels. Qualitative and morphometric characters were analysed in three environments, being useful to significantly separate mussels from each area inside and outside the port. Results were insufficient to discriminate similarities or differences meaningful of one or two species.